MOTIVASI KUNJUNGAN WISATAWAN PADA EVENT PESTA PANTAI INDAH SELATBARU DI KABUPATEN BENGKALIS - Eva Dahlia Nainggolan; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Motivation is a change of power within a person aharacterized by an effective impulse related to one’s desire to be respected, respected in order to fulfill personal ambition. The research was to analyze the motivations of tourists visiting the indah beach of selatbaru . District Bengkalis. To know the constraints of the event beautiful beach party celebration selatbaru,this study using quantitative descriptive method,to describe the problem in the tourist visit samples used are 100 people. Based on the results of the research that has been done, retrieved the motivation of tourists visit to the indah selatbaru of bengkalis is influenced by a variety of motivation, such as physical motivation, motivation fantasy social and ciltural motivation.while the obstacles faced in organizing a beautiful beach party event selatbaru namely vehicle traffic jams and parking problems.Keywords : motivation intrinsic and ekstrinsik, motivation, tourist